Pengaruh Country Of Origin Dan Word Of Mouth Terhadap Keputusan Pembelian Smartphone Samsung (Study Kasus Mahasiswa Feb Unisma) - Farkhan Azis; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2020)
Abstract This research was conducted to determine the effect of Country of Origin and Word of Mouth on the decision to purchase Samsung smartphones in the Faculty of Business Economics, Islamic University of Malang. This research uses explanatory research and quantitative approaches. Malhotra theory is used to take samples, namely the number of items x 5 so that a total sample of 90 people is found.To solve the proble in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. research using multiple linear regression analysis with the help of SPSS 25. 0 The results of this study are the Country of Origin and Word of Mouth variables influence simultaneous purchasing decisions, partially the Country of Origin and Word of Mouth variables influence the Samsung Smartphone Purchasing Decisions at the Faculty of Business Economics, a Islamic University of Malang.